Investigation of traction and dynamic properties of wheeled vehicles with electric and hybrid power plants on the test stands with running drums - P. A. Kiselyov; A. I. Fedotov; O. S. Yan’kov; S. N. Krivtsov (Вестник СибАДИ, 2025)
Introduction. Modern wheeled vehicles with electric and hybrid power plants are becoming more and more widespread. It is obvious that with the increasing number of wheeled vehicles with electric and hybrid power plants, there is a need to conduct a full-fledged and qualitative study of the working processes of wheeled vehicles both at the stages of production and fine-tuning at manufacturing enterprises, and in operating conditions at the service stations and other organizations. The research of the technical condition of a wheeled vehicle with electric and hybrid power plants with a classic layout of the power unit and transmission (front or rear axle drive) is quite possible to be conducted on existing stands. But when testing wheeled vehicles with electric and hybrid power plants with all-wheel drive or with an electric motor generator for each drive wheel, a problem arises due to the lack of methods and means to measure traction force on each wheel individually.Materials and methods. This section provides an analysis of the possibilities of conducting a study of the technical condition of wheeled vehicles with electric and hybrid power plants on modern power and inertia stands that apply the principle of reversibility of motion.Results. Methods have been developed to study the traction and dynamic properties of wheeled vehicles with electric and hybrid power plants, to implement it was proposed to use developed research stand complex, which includes a hybrid stand with control and measuring systems that allow to determine forces and power on the driving wheels of vehicles, as well as time and kinematic parameters of its functioning process. During the experimental studies, the results of Kia Soul EV and Toyota Prius NHW20 operation processes were obtained, their power and kinematic parameters were analyzed.Conclusion. As a result of the study, it has been proved that in order to ensure highly informative and stable test modes of wheeled vehicle’s operation in the process of studying their traction and dynamic properties, it is necessary to use hybrid stands.